Reliability model developing for protective fittings taking into account load-sharing effect - Щербовських, Сергій Володимирович; Стефанович, Тетяна Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
The mathematical reliability model of protective fittings for the pressure vessel was developed in the paper. The model is intended for the quantitative analysis of the system failure causes. System reliability was formalized by a dynamic fault tree with the set logical conditions of load sharing. Reliability characteristics were calculated based on the split homogeneous Markov model. The split Markov model implies that the operating time of the protective fitting components is distributed according to the Weibull law. The scientific value of the model lies in the fact that it takes into account the load-sharing effect in the three-way tap, safety valves and overpressure valve on the system failure probability. The result of the simulation is a family of probabilistic curves, obtained for different values of load-sharing ratios. The dependence of the change in the main cause of the system failure on the change in these ratios was shown.